Interaksi Sosial Guru dan Orang Tua Siswa dalam Proses Pembelajaran Daring di Masa Covid -19 Madrasah Ibtidaiyah Bayanul Ulum Punggur Kecil Sungai Kakap - Imam Sanusi (IBTIDA', 2020)
Covid-19 is already familiar to parents of students, even with the rumors of the covid-19 virus making learning in schools use online, the problem of social interaction between teachers and guardians of students is often seen in print media and even on electronic media / television. It has become a trending topic material and is often discussed, almost every day there are students who have problems regarding interactions with their teachers regarding the online learning process which is always associated with their teachers and even the handling involves subject teachers.In this interaction problem the writer uses a descriptive method with a quantitative narrative approach, the writer describes what is happening in the field based on the facts that occur, while the location of this research is located in Parit H. Maksum Punggur Kecil Sungai Kakap. The research data were obtained from teachers and parents regarding the problem. social interactions during the Covid-19 period. As for the means of collecting data, researchers obtained by means of observation, direct interviews with teachers or parents of students then researcher analysis. Social interactions that are less solid will cause conflict and most often occur between teachers and parents of students due to miscommunication between teachers / school authorities and student guardians. Therefore, to carry out or overcome mis communication and increase social interaction to reduce conflict can be done in various ways, as follows: (1). Conduct regular meetings, (2) carry out family education, (3). Socializing school programs and procedures, (4). Protect students and teaching staff, (5). Complete facilities and infrastructure in schools